Selected aspects of the restriction of trading in agricultural real estate under Polish law in the context of the EU principle of free movement of capital - Wojciechowski, Paweł (Przegląd Prawa Rolnego, 2020)
The aim of the considerations was to assess the admissibility of restrictions of trading in agricultural real estate introduced by the Act on shaping the agricultural system in the context of the EU principle of free movement of capital. The article presents the economic and climatic phenomena that have been taking place worldwide and in the European Union in particular, which make the introduction of legal solutions limiting trading in agricultural land inevitable. The EU principle of free movement of capital is discussed, including the premises for the admissibility of restrictions of this principle. In the light of these findings, an assessment of instruments that restrict trading in agricultural real estate has been made. The analysis carried out in the article leads to the conclusion that most of the adopted solutions pass the test of admissibility of introducing restrictions that has been developed in the case law of the Court of Justice of the European Union. Some of these restrictions, however, raise doubts.